BEHAVIORAL BIASES IN INVESTMENT DECISIONS: FINANCIAL LITERACY AND SOCIAL IMPACT AWARENESS AS MODERATOR - Priscilla Appianin Affram; Maya Sari; Nugraha; Iqbal Lutfi (RADJA PUBLIKA, 2026)
This study examines the influence of behavioural biases on investment decisions among graduate-educated retail investors affiliated with Universitas Pendidikan Indonesia, while investigating the moderating roles of financial literacy and social impact awareness. Adopting a quantitative research design, data were collected from 322 respondents through a cross-sectional survey and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results demonstrate that behavioural biases exert the strongest positive direct effect on investment decisions, confirming that cognitive tendencies such as overconfidence, anchoring, and herding significantly shape decision-making regardless of educational background. Furthermore, financial literacy and social impact awareness show statistically significant positive direct effects on investment behaviour, indicating that both analytical financial knowledge and sustainability-oriented considerations contribute to more disciplined investment outcomes. However, the study finds that neither financial literacy nor social impact awareness significantly moderates the relationship between behavioural biases and investment decisions, suggesting that these cognitive biases are deeply rooted and cannot be fully neutralized by financial knowledge or ethical awareness alone. These findings highlight the persistent influence of behavioural factors in modern digital investment environments and underscore the complexity of investor behaviour among educated cohorts.